2020
DOI: 10.1136/bmjopen-2020-038578
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of low-magnitude high-frequency vibration (LMHFV) on musculoskeletal health of participants on wheelchair: a study protocol for a single-blinded randomised controlled study

Abstract: BackgroundOsteoporosis is an age-related disease with progressive loss of bone, leading to fragile bone. It is one of the major health issues in older adults and causes medical, social and economic impacts globally. Patients with osteoporosis have high risk of osteoporotic fractures. Low-magnitude high-frequency vibration (LMHFV) is a non-invasive biophysical intervention providing whole-body mechanical stimulation. Previous studies showed that LMHFV is beneficial to muscle strength, postural control, balancin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 29 publications
1
12
0
Order By: Relevance
“…Vibration therapy can improve physical properties and reduce the negative effects of aging on bones, muscles and tendons. Low amplitude high frequency vibration is beneficial to muscle strength, posture control, balance ability, new bone formation, spinal bone mineral density, and blood circulation [17] . Vibratory exercise improves bone health by directly triggering bone reaction mechanisms and triggering powerful muscles that strengthen exoskeleton contractions [18,19] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Vibration therapy can improve physical properties and reduce the negative effects of aging on bones, muscles and tendons. Low amplitude high frequency vibration is beneficial to muscle strength, posture control, balance ability, new bone formation, spinal bone mineral density, and blood circulation [17] . Vibratory exercise improves bone health by directly triggering bone reaction mechanisms and triggering powerful muscles that strengthen exoskeleton contractions [18,19] .…”
Section: Discussionmentioning
confidence: 99%
“…Low amplitude high frequency vibration is beneficial to muscle strength, posture control, balance ability, new bone formation, spinal bone mineral density, and blood circulation. [17] Vibratory exercise improves bone health by directly triggering bone reaction mechanisms and triggering powerful muscles that strengthen exoskeleton contractions. [18,19] Evidence shows that a small signal is a contributing bone signal when it acts on the bone at a higher frequency.…”
Section: Discussionmentioning
confidence: 99%
“…Muscle strength and muscle performance are the primary outcomes of this study 22 23. Handgrip strength will be measured using a dynamometer (5030JI, JAMAR, IL, USA) on each hand of the participants.…”
Section: Methods and Analysismentioning
confidence: 99%
“…Moreover, low magnitude high frequency vibration (LMHFV) has been proven as an alternative to conventional exercise that can stimulate metabolic responses [ 22 ]. In preclinical and clinical studies, LMHFV has been reported to have benefits on muscle contractibility functions [ 23 ], muscle structures and strength [ 24 ]. It has also been proven to be effective in inducing tissue regeneration and promoting blood flow [ 25 ].…”
Section: Introductionmentioning
confidence: 99%